Coincidental detection of genomes of porcine parvoviruses and porcine circovirus type 2 infecting pigs in Japan - Prayuth Saekhow (2018)
© 2015 The Japanese Society of Veterinary Science. The infection status of 15 viruses in 120 pigs aged about 6 months was investigated based on tonsil specimens collected from a slaughterhouse. Only 5 species of porcine parvoviruses and porcine circovirus type 2 (PCV2) were detected at high frequencies; 67% for porcine parvovirus (PPV) (PPV-Kr or -NADL2 as the new abbreviation), 58% for PPV2 (CnP-PARV4), 39% for PPV3 (P-PARV4), 33% for PPV4 (PPV4), 55% for PBo-likeV (PBoV7) and 80% for PCV2. A phylogenetic analysis of PPV3 suggested that Japanese PPV3s showed a slight variation, and possibly, there were farms harboring homogeneous or heterogeneous PPV3s. Statistical analyses indicated that the detection of PCV2 was significantly coincidental with each detection of PPV, PPV2 and PPV3, and PPV and PPV4 were also coincidentally detected. The concurrent infection with PCV2 and porcine parvoviruses in the subclinically infected pigs may resemble the infection status of pigs with the clinical manifestations of porcine circovirus associated disease which occurs in 3–5 months old pigs and is thought to be primarily caused by the PCV2 infection.